(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article focuses on the fact that creativity for the teacher is a relevant component of his professional activity, a way of self-realization, sup- port in the development of the personality of others. The diversity of pedagogical activity which is directed not only at creation of pedagogical technologies, but also at values of pupils is the es- sential basis of development of personality of the creative teacher is proved. The content and structure of personality of a creative teacher in foreign theory and practice are investigated. It is proven that a creative prod- uct is the result of a specific human action that is influenced by a particular environment. personality, intelligence and temperament, as well as body structure, character traits, habits, attitudes, self-esteem, value systems, mechanisms of protection and behavior. The main components of a teacher’s professional activity, in particular his knowledge and skills, namely didactic, communication, organiza- tional, scientific and creative, are distinguished. It is found that the important features of a creative teacher are the awareness of their own creative abilities and creativity, belief in themselves, respect for others, empathy, enthusiasm and expression, courage in accepting risky and non-standard situations, competence and curiosity asso- ciated with a high level of intelligence and self-perfection, attractiveness and originality, artistic sense and creative imagination, ’open mind’ and independence of thinking, tolerance, self-organization, activity, vitality and flexibility at work. It is proved that the creative teacher is characterized by high level of pedagogical creativity, possesses the traits of creative personality, mo- tives, abilities that contribute to successful creative pedagogical activity.